Partners in Health - Centre for Access to Services in English (CASE) (2021)

The Importance of Resurrecting English-speaking Healthcare Services in Québec - Jackson-Cappuccino, Ella (Youth for Youth Québec (Y4Y Québec), 2021)
French is the first language of 71.2% of Quebecers. For the remaining 27.9%, communication outside of this language can be difficult, especially in regard to health care (Ouimet et. al 3).This is of concern as those who seek medical attention or health resources may not be provided adequate care given the linguistic barrier. Particularly, it is Québec’s Englishspeaking minority that is most affected by this issue (Ouimet et. al 3). Within this minority, there are still hundreds of thousands of English-speaking individuals who desire to seek health services in their first official language. The wish does not simply arise due to a lack of bilingualism. Evidence shows that in times of crisis - when individuals look to communicate a matter of importance - they most often revert to their mother tongue (Silver 686). Without resources designed to cater to the English-speaking population, the government subjects this linguistic minority group to unequal health care services.

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

Réduction des services dans les CLSC de la Basse-Côte-Nord - Buffitt, Kimberly (2021)

Reduction in Services at the CLSC's on the Lower North Shore - Buffitt, Kimberly (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Establishing a Community Task Force on Mental Health : Exploring the Role of Minority Language Communities in Improving Access to Mental Health Services - Mental Health & Wellness Gaspésie (2021)
Keywords: Official Language Minority Community (OLMC)

Evaluation of the Quebec Community Health and Social Service Foundation's (QCHF) Patient Navigator Project - Anastasopoulos, Vanessa (2021)

Overcoming Language Barriers in Health and Social Services - Bilodeau, Nancy (2021)

CHSSN Survey to Access to English-language Health and Social Services - Community Health and Social Services Network (CHSSN) (Building Together, 2021)

How Services Can Better Address the Realities of English-Speaking Fathers - Community Health and Social Services Network (CHSSN) (2021)
A report based on an analysis of recent surveys and public data, identified five essential ways family services can better address the realities of English-speaking fathers.

2021 Virtual Conference : Addressing Access to Health Care and Social Services for Language Minorities : Best Practices and Latest Evidence - Dialogue McGill (2021)

Conférence virtuelle 2021 : Accès aux soins de santé et aux services sociaux pour les minorités linguistiques : pratiques exemplaires et les résultats probants - Dialogue McGill (2021)

Rapport à la communauté : Faits saillants de 2019-2021 et aperçu de nos orientations - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Report to the community : Highlights from 2019-2021 and overview of where we’re headed - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Understanding the Experience of English-speaking Seniors in Quebec : Accessing and Interacting with Health and Social Services and the Effect on Health Outcomes - Recreo Therapy (Community Health and Social Services Network (CHSSN), 2021)

East Island Community Sector Internship Opportunities - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)